2022
DOI: 10.1111/ahe.12859
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the usage of YouTube videos about Histology and Embryology as an educational material

Abstract: The use of YouTube videos for educational purposes has been increasingly popular.The quality and accuracy of the information level of these videos should be checked by expert trainers. This study aims to evaluate the content, quality and functionality of YouTube videos on Histology and Embryology and to measure their educational usefulness. In the study, searches were performed using the keywords "Histology" and "Embryology" in the YouTube search tab. Quality and content were evaluated using the Video Power In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…On the basis of our study, we think that YouTube videos about anatomy are of medium quality. Similarly, Cetinavci et al (2022) found that histology-embryology YouTube videos were of moderate quality. We also found that videos with excellent TCSs had significantly higher GQS scores (p < 0.001).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…On the basis of our study, we think that YouTube videos about anatomy are of medium quality. Similarly, Cetinavci et al (2022) found that histology-embryology YouTube videos were of moderate quality. We also found that videos with excellent TCSs had significantly higher GQS scores (p < 0.001).…”
Section: Discussionmentioning
confidence: 95%
“…In our study, the modified DISCERN and JAMA scores were statistically significantly higher for videos that were useful than for those that were not useful. Similarly, Cetinavci et al (2022) analyzed 50 videos and found that the modified DISCERN and JAMA scores were significantly higher for the useful ones. Raikos and Waidyasekara (2014) suggested on the basis of Anatomical Content Scores that YouTube videos on heart anatomy were inadequate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A modified DISCERN score (Quality Criteria for Consumer Health Information) was used to analyze the reliability and quality of the videos, 17,18 which consisted of five questions, and 1 point was given for every Yes and 0 points for every No. Specifically, five criteria were used: (1) the video was clear, concise, and understandable; (2) the sources of utilized information were reliable; (3) the presented information was balanced and unbiased; (4) additional sources of information were listed for patient reference; and (5) areas of uncertainty/controversy were mentioned 19 …”
Section: Methodsmentioning
confidence: 99%
“…Specifically, five criteria were used: (1) the video was clear, concise, and understandable; (2) the sources of utilized information were reliable; (3) the presented information was balanced and unbiased; (4) additional sources of information were listed for patient reference; and (5) areas of uncertainty/controversy were mentioned. 19…”
Section: Assessment Of Content and Quality Of Videosmentioning
confidence: 99%